The Network of Services for COVID-19 Vaccination in Persons With Mental Disorders: The Italian Social Health System, Its Organization, and Bioethical Issues - Scendoni, Roberto; Fedeli, Piergiorgio; Cingolani, Mariano (Frontiers in Public Health, 2022)
The adoption of restrictive measures aimed at curtailing the spread of SARS-CoV2 has had a harmful impact on socio-affective relationships, while limiting the scope of interventions and activities to promote social inclusion, with considerable negative repercussions for patients with mental disorders. Vaccination has been and will continue to be a valid tool to overcome the barriers of social isolation and to protect the health of this category of patients. In this paper we present an overview of the Italian network of social and healthcare services for COVID-19 vaccination among patients with mental disorders. Some aspects of medical ethics are discussed in order to share good practices for improving the health of this vulnerable group of people. We then consider the measures implemented by the health system in Italy to deal with the phenomenon of vaccine hesitancy before addressing the issue of autonomy and restricted access to vaccination points. Finally, we illustrate some of the perspectives already adopted by the Italian system, which may be useful to the global scientific community